How to succeed at the medical interview - Smith, Chris, 1976-; Meeking, Darryl (Chichester, West Sussex, UK ; Hoboken, NJ, USA : Wiley-Blackwell, BMJ Books, 2013)
Details the types of questions that will be asked at medical interviews and also provides improved guidance for overseas doctors and healthcare professionals and for those seeking to practice abroad.
The medical interview -- Preparing for the interview -- Performing at the interview -- Common interview questions -- Interview questions that test your knowledge -- Interview questions that test your generic skills -- Competency-based tasks.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Medicine -- Vocational guidance -- Great Britain; Physicians -- Employment -- Great Britain; Employment interviewing -- Great Britain; Interviews as Topic; Job Application; Physicians; MEDICAL -- Physicians; Employment interviewing; Medicine -- Vocational guidance; Physicians -- Employment; Great Britain; Great Britain; Electronic books; Electronic books